Current Population Survey, October 1991: School Enrollment ([Verlag nicht ermittelbar], 1993)
Data on labor force activity for the week prior to the survey are supplied in this collection. Information is available on the employment status, occupation, and industry of persons 15 years old and over. Demographic variables such as age, sex, race, marital status, veteran status, household relationship, educational background, and Spanish origin are included. In addition to providing these core data, the October survey also contains a special supplement on school enrollment. This supplement includes the following items: current grade attending at public or private school, whether attending college full- or part-time at a two- or four-year institution, year last attended a regular school, and year graduated from high school.